Preliminary checklist of orchids from Ulu Endau, Johore, Malaysia - Yussof, Shaharin; Kiew, Ruth; Lim, Weng Hee; Ibrahim, Nuraini (Malaysian Nature Society, 1987)
The orchid family is the largest family of flowering plants in Peninsular Malaysia with an estimated 100 genera and. 846 species (Holttum, 1964). The species which produce large, showy and long lasting flowers. are much sought after by horticulturalists, gardeners and orchid breeders. Even some less showy ones are in demand as they can be used in hybridization to impart certain desired attributes, such as unusual colour or pattern, longer shelf-life, floriferousness etc., to their offspring